The Role of the Special Criminal Unit for the Criminal Investigation Unit in Dealing with Online Fraud Crimes in Bogor City Police Jurisdiction - Muhammad Faizal (Police Studies Review, 2021)
This study aims to analyze the role of the Criminal Investigation Unit of the Bogor City Police Criminal Investigation Unit in dealing with online fraud in the Bogor City Police area. The conceptual literature used is Information Technology Concept, Role Theory, and POAC Management Theory. This study uses a qualitative approach with field research methods (field research). Sources of data include 1) Head of Bogor City Police, 2) Head of Criminal Investigation Unit of Bogor City Police, 3) Deputy Head of Criminal Investigation Unit of Bogor City Police, 4) Investigator of the Criminal Investigation Unit of the Bogor City Police. The results of the study show that 1) The investigation of online fraud crimes is still not optimal because if you look at the number of settlements for online fraud crimes, it is not proportional to the number of existing online fraud crimes. So this is a special concern because crime is now increasingly developing using information media and information technology; 2) The influencing factors in dealing with online fraud are influenced by internal and external factors so that this becomes an obstacle in dealing with online fraud crimes; 3) The role of the Criminal Investigation Unit in dealing with online fraud crimes must be of particular concern because crime continues to grow using information technology media. So there needs to be development and innovation in conducting investigations so that the settlement of online fraud crimes can be done more easily and get maximum results. So the use of tools and information technology in uncovering non-criminals needs to be increased so that the investigation becomes more maximal and effective. It will be even more focused on dealing with online fraud by forming a special cyber unit that handles cyber crimes including online fraud itself. So that the investigation and investigation can be maximized.